Progress in GABAA receptor agonists for insomnia disorder - Wang, Weiyi; Fu, Wanting; Zhu, Hongyan; Ma, Jing; Zhang, Jian; Qi, Jia (Frontiers in Pharmacology, 2024)
Insomnia is the most common sleep disorder in which an individual has trouble falling or staying asleep. Chronic sleep loss interferes with daily functioning and adversely affects health. The main clinical drugs for insomnia are the positive allosteric modulator of the GABA (gamma-aminobutyric acid) A receptors (GABAARs) at the benzodiazepine site with selectivity of the GABA-α1 receptor. They are divided into benzodiazepine drugs and non-benzodiazepine drugs. Most recently, the first partial positive allosteric modulator of GABAAR Dimdazenil was approved by National Medical Products Administration (NMPA) and launched in China. This review summarized the mechanism of actions of current clinical drugs for insomnia, and the clinical applications of these drugs, which may help to understand their involvement in insomnia, and to search for more selective and potent ligands to be used in the treatment of insomnia.